Implementation of Curriculum Innovation and Islamic Education Learning Basic Education/Implementasi Inovasi Kurikulum dan Pembelajaran Pendidikan Agama Islam Pendidikan Dasar - Triyo Supriyatno; Umi Salamah (Al-Mudarris: Journal Of Education, 2020)
This study purposes to explore curriculum innovation and PAI teaching at SDIT Ahmad Yani in Malang. This research used qualitative approach with four research questions: How does the curriculum innovation, strategy, and media of PAI learning in SDIT Ahmad Yani Malang?Â  Data collection was ended through interviews, observation and documentation. The results of the study are: The Learning used 2013 curriculum with a scientific-based approach, and KTSP curriculum. The model of learning is a goal-oriented, but the majority has lifted towards the process and achievement of competence, although not total. Applied learning methods have also experienced innovation in order to support a smooth learning. Media was used fairly well, but in order to support a smooth and achievement of learning in line with the principles alive in the curriculum applied, this fact needs to be improved towards better, both in terms of accuracy, presentation and materials used.